Inhibited Maternal Bone Resorption Suppress Fetal Rat Bone Development During Pregnancy - Jia, Huanhuan; Rao, Li; Miu, Kai Kei; Tang, Shuangjie; Chen, Wei; Yang, Guozhu; Li, Yuying; Li, Qingnan; Chen, Jun; Lu, Li (Frontiers in Cell and Developmental Biology, 2020)
Objective: To determine the relationship between maternal bone resorption and bone development in fetuses. Methods: Female SD rats were injected with fluorescent calcium indicator calcein or/and tetracycline 1 week before pregnancy, followed by fluorescence detection in fetal tibias 21 days post-treatment. Alendronate was subsequently administered to pregnant rats to inhibit maternal bone resorption, while maternal bone turnover and fetal bone development were both examined. Results: The maternal fluorescent labeled calcium before pregnancy was found in the fetal tibia. It is indicated that the calcium of maternal bones may be released into the maternal circulation through high bone resorption during pregnancy, thereby participating in the fetal bone development. Bone histomorphometry and serum biomarker results showed that Alendronate significantly inhibited maternal bone resorption in pregnant rats when compared to normal pregnant rats. Moreover, the body weight, bone mass and bone length of the fetuses in the Alendronate group were significantly decreased; while no apparent abnormality in placental morphology was observed. The above results implied that when maternal bone resorption is suppressed, the development of the fetal bone shall also be suppressed. Conclusion: Calcium in the maternal bone is released into the maternal circulation through bone resorption during pregnancy which represents an important material source in fetal bone development. Therefore, high bone turnover during pregnancy is essential for mammalian embryonic bone development.